Public Opinion Monitoring and Guidance Analysis in the Process of News Dissemination from the Perspective of Big Data - Shi, Wei; Qin, Weiwei (Computing and Informatics, 2024)
In order to improve the positive effect of news communication, this paper conducts research on the detection and analysis of public opinion in the process of news communication from the perspective of big data and analyzes the guidance of news communication public opinion. Combined with the actual needs of news dissemination, the numerical accuracy, convergence order, numerical convergence and numerical stability of the SS-CSPH method are mainly analyzed and discussed according to the results of numerical simulation. Moreover, this paper confirms that the smooth function and smooth length do have an impact on the solution of the Strang split-corrected smoothed particle hydrodynamics method (SS-CSPH). In addition, this paper constructs a public opinion monitoring and guidance system in the process of news dissemination. From the simulation evaluation results, it can be seen that the method of public opinion detection and guidance in the process of news dissemination proposed in this paper can play a certain role in the monitoring and guidance of news public opinion.